2022
DOI: 10.1159/000524344
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Glial Fibrillary Acidic Protein Astrocytopathy Presenting with Area Postrema Syndrome-Like Symptoms without Medulla Oblongata Lesions

Abstract: <b><i>Introduction:</i></b> Autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy is a recently described steroid-responsive meningoencephalomyelitis positive for cerebrospinal fluid (CSF) anti-GFAP antibody. Area postrema syndrome (APS) involves intractable hiccups, nausea, and vomiting, which is caused by medulla oblongata (MO) impairment. APS is a characteristic symptom of aquaporin-4 (AQP4) autoimmunity, and it helps to differentiate between AQP4 and GFAP autoimmunity. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Since 2018, several studies have noticed that APS could be a symptom of autoimmune GFAP astrocytopathy. [10][11][12][13][14][15][16][17][18] However, the incidence of APS in this disorder is unknown. We found that 8 of the 74 patients (11%) with autoimmune GFAP astrocytopathy presented with APS and the frequency of APS as the onset symptom is 4%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2018, several studies have noticed that APS could be a symptom of autoimmune GFAP astrocytopathy. [10][11][12][13][14][15][16][17][18] However, the incidence of APS in this disorder is unknown. We found that 8 of the 74 patients (11%) with autoimmune GFAP astrocytopathy presented with APS and the frequency of APS as the onset symptom is 4%.…”
Section: Discussionmentioning
confidence: 99%
“…10 Thereafter, APS was increasingly reported as a noticeable manifestation of this disorder. [11][12][13][14][15][16][17] However, the incidence and phenotypes of APS in autoimmune GFAP astrocytopathy have not been described comprehensively.…”
mentioning
confidence: 99%
“…9, 10 For patients with brainstem syndromes and area postrema symptoms (ie, intractable hiccups, nausea and vomiting, or involvement around the medulla oblongata) anti-aquaporin-4 or anti-GFAP antibody associations should be considered (see Optic Neuropathy section). 50 Isolated cochleovestibulopathy has rarely been reported as a paraneoplastic syndrome related to a variety of tumors, but no characteristic tumor or antibody has been described. 51 CEREBELLAR SYNDROMES Anti-PCA-1 (Yo) antibodies remain the most commonly recognized association with paraneoplastic cerebellar syndromes and predominantly occur in women KEY POINT…”
Section: Iglon5-associated Syndromesmentioning
confidence: 99%
“…For patients with brainstem syndromes and area postrema symptoms (ie, intractable hiccups, nausea and vomiting, or involvement around the medulla oblongata) anti–aquaporin-4 or anti-GFAP antibody associations should be considered (see Optic Neuropathy section) 50 …”
Section: Brainstem Syndromesmentioning
confidence: 99%
“…Transverse myelitis and ON also occur frequently in GFAP-A [ 2 ]. Area postrema syndrome (APS) is considered as one of the symptoms of GFAP astrocytopathy [ 3 ]. We currently report a rare case of AQP4 and GFAP double-positive NMOSD complicated with ovarian teratoma, presenting with APS, long-segment myelitis, and encephalopathy.…”
mentioning
confidence: 99%